CRISPR/Cas9 treatment causes extended TP53-dependent cell cycle arrest in human cells. Issue 16 (20th July 2020) - Geisinger, Jonathan M; Stearns, Tim
Abstract: While the mechanism of CRISPR/Cas9 cleavage is understood, the basis for the large variation in mutant recovery for a given target sequence between cell lines is much less clear. We hypothesized that this variation may be due to differences in how the DNA damage response affects cell cycle progression. We used incorporation of EdU as a marker of cell cycle progression to analyze the response of several human cell lines to CRISPR/Cas9 treatment with a single guide directed to a unique locus. Cell lines with functionally wild-type TP53 exhibited higher levels of cell cycle arrest compared to lines without. Chemical inhibition of TP53 protein combined with TP53 and RB1 transcript silencing alleviated induced arrest in TP53 +/+ cells. Using dCas9, we determined this arrest is driven in part by Cas9 binding to DNA. Additionally, wild-type Cas9 induced fewer 53BP1 foci in TP53 +/+ cells compared to TP53 −/− cells and DD-Cas9, suggesting that differences in break sensing are responsible for cell cycle arrest variation. We conclude that CRISPR/Cas9 treatment induces a cell cycle arrest dependent on functional TP53 as well as Cas9 DNA binding and cleavage. Our findings suggest that transient inhibition of TP53 may increase genome editing recovery in primary and TP53 +/+ cell lines.